Barriers to agricultural employment among African American youth: Evidence from the American Community Survey - Anthony Baffoe-Bonnie; Fafanyo Asiseh; Obed Quaicoe (PLoS ONE, 2025)
This paper investigates the occupational choices of African American youth in U.S. agricultural and food sectors. Using nationally representative data from the American Community Survey, we estimate a multinomial logit model to assess how socioeconomic conditions influence employment in three occupational categories: farming, farm-related work, and food preparation. Results reveal that agricultural employment among African American youth remains rare, and that gender is a strong predictor of occupational choice. Young African American women are significantly less likely than men to work in farming or related sectors, and more likely to be employed in food preparation. Educational attainment and student status are positively associated with food service employment but do not predict participation in farming occupations. These findings have important implications for agricultural policy, particularly as policymakers seek to address demographic disparities and revitalize the rural workforce. The results highlight the need for youth-specific policies, including targeted outreach, farm incubator programs, and access to capital, that address the compounded barriers facing youth in agricultural employment.